Streptococcus salivarius Probiotics to Prevent Acute Otitis Media in Children: A Randomized Clinical Trial - Sarlin Suvi; Koskela Ulla; Honkila Minna; Tähtinen Paula A.; Pokka Tytti; Renko Marjo; Tapiainen Terhi (JAMA Network, 2025)
Importance
New approaches for the prevention of acute otitis media (AOM), the most common reason for antibiotic use in children, are needed.
Objective
To assess the efficacy of the Streptococcus salivarius K12 oral probiotics in the primary prevention of AOM.
Design, Setting, and Participants
This double-blind, randomized placebo-controlled clinical trial was conducted from August 1, 2020, to May 31, 2021, at 50 day care centers in the Oulu region of Finland. A total of 827 children aged 1 to 6 years attending day care were included. The exclusion criteria consisted of ongoing antimicrobial prophylaxis or immunodeficiency. The follow-up time was 6 months and was completed on May 31, 2021. Data were analyzed from October 24, 2022, to September 16, 2023, based on intention to treat.
Intervention
Eligible participants were randomly allocated to receive 1 daily dose of a S salivarius K12 product or placebo every evening for 6 months. A daily dose was defined as 1 sachet of soluble oral powder for children younger than 3 years or 1 chewable tablet for children 3 years or older containing 1 × 109 colony-forming units of S salivarius K12.
Main Outcomes and Measures
The primary outcome was the proportion of children with at least 1 episode of AOM requiring antimicrobial therapy within 6 months of randomization. All physician visits and purchases of antimicrobial drugs were retrieved from the electronic national medical record and prescription register. The primary outcome was met if the legal guardian had purchased an antimicrobial prescription for AOM.
Results
A total of 827 children with a mean (SD) age of 4.1 (1.6) years (433 boys [52.4%]) were randomized to S salivarius K12 oral products (n = 413) or placebo (n = 414). Thirty-four children (8.2%) in the S salivarius group and 24 children (5.8%) in the placebo group experienced at least 1 episode of AOM requiring antimicrobial therapy during the 6-month follow-up period (relative risk, 1.42 [95% CI, 0.86-2.34]; proportion difference, −2.44% [95% CI, −5.94% to 1.09%]; P = .17). Time to first AOM episode did not differ between the groups (174 [95% CI, 171-177] days in the S salivarius group vs 176 [95% CI, 173-179] days in the placebo group; P = .18).
Conclusions and Relevance
In this randomized placebo-controlled clinical trial, the daily use of the S salivarius K12 products for 6 months did not reduce the occurrence of AOM. New approaches for primary prevention of AOM among children are needed.